A first order assessment of the moving granular panel filter - Shaw, Gareth D. H (Department of Social Development, 2024)
The capabilities of a specific moving granular panel bed filter are investigated, highlighting FBC flue gas cleanup. The continuous operability offers some advantages over the discontinuous operating mode of the static filter bed but the effects of moving granular medium are found to introduce other disadvantages not originally anticipated. Movement of granular medium resulted in significantly reduced filtration efficiencies with respect to static granular beds for the same operating conditions. Pressure drop analysis indicated voidage increases within the bed with granular movement but the increases were not considered significant enough to explain the reduced efficiencies suffered by the moving filter medium . Reentrainment at high Stokes numbers is considered to be the main contributor for reduced filter ability. An empirical correlations was developed to model the re-entrainment effects. The causes and effects of non uniform granular flow were highlighted resolved by modification to the panel design. The modifications involved the inclination of the panel a few degrees off the vertical. The precise angle was found to depend on fluid flowrate through the filter medium. The ability of the continuous medium replenishment to maintain low fluid pressure drop was demonstrated. The concept of initial collection efficiency, used in static granular beds as a conservative measure of the filter efficiency in granular filter design, is shown not to be applicable to moving granular beds. Collection efficiencies were found to deteriorate progressively from initial clean granule conditions. Increase in panel thickness is shown to be necessary to improve the filter efficiency to that required to meet the emission regulations. The resulting increased operating pressure drop is calculated to be in the order of that imposed by an equivalent electrostatic precipitator making the design, an attractive low pressure drop filter, assuming sufficient improvement in collection efficiency can be achieved with the increased panel thickness. Order of magnitude cost estimates are presented at two different scales. Comparisons of costs with conventional filter designs show the design to be worth further investigation.